Broadcast control of multi-agent systems with instability phenomenon - M. H., Mohamad Nor; Z. H., Ismail; Mohd Ashraf, Ahmad (IEEE, 2017)
This paper presents the instability problem of a broadcast control framework for multi-agent systems in executing certain motion coordination tasks. First, response of unstable solution using a standard broadcast control framework is demonstrated by choosing one motion coordination task as an example of the unstable case. In order to solve the problem, the standard broadcast control framework has been modified, where deterministic movements of the agents are limited to a certain value. Finally, the chosen motion coordination task has been simulated back using the modified broadcast control framework and numerical simulation illustrated the effectiveness of the modified broadcast control framework in handling the instability case.